Adenoid cystic carcinoma of the larynx: Case report and review of literature - Fatima Zahra Es-Sahli; Achraf Amine Sbai; Anass Haloui; Drissia Benfadil; Amal Bennani; Azzedine Lachkar; Adil ABDNBI Tsen; Fahd El Ayoubi (Radiology Case Reports)
Adenoid cystic carcinoma (ACC) is a rare malignant neoplasm arising in both major and minor salivary glands. It represents approximately 1% of all head and neck cancers and about 10% of salivary gland tumors. Laryngeal adenoid cystic carcinoma (LACC) is a rare entity that most frequently arises in the subglottic region. It is characterized by slow progression, perineuronal invasion, frequent local recurrences and delayed distant metastasis. Surgical resection remains the gold standard for the treatment of ACC; however, the role of adjuvant radiotherapy and prophylactic neck dissection remains uncertain and is widely debated in the literature.This case report describes a 60-year-old male patient who presented with progressive dysphagia and worsening dyspnea. Clinical evaluation, including computed tomography (CT), revealed a lesion involving the left glottic and supraglottic regions. Biopsy obtained via direct laryngoscopy confirmed the diagnosis of laryngeal adenoid cystic carcinoma (LACC). The patient subsequently underwent total laryngectomy with adjuvant radiotherapy.